Multi-scale water resources assessment in Awash Basin, Ethiopia - Taye, Meron Teferi; Seid, Abdulkarim; Tekleab, S.; Tilaye, R.; Abebe, S.; Admassu, W.; Bitew, A.; Abdulkadir, O.; Mohammed, M.; Berhanu, B. (International Water Management Institute, 2024)
Water resources management under a changing climate requires a multi-scale water resources understanding of a given basin. The Awash River Basin of Ethiopia is experiencing various water management challenges due to its complex hydro-climatological conditions and a range of water users, hence understanding the anthropogenic impacts on hydrological changes is complex. The study is aimed at improving the climate resilience of water management practices at multiple spatial scales. This report is a synthesis of the multi-scale water resources assessment of the Awash Basin. The objectives are: (1) characterization of the basin’s distribution and availability of water; (2) identification of the existing water resources planning and management practices; (3) challenges at multiple scales; and (4) developing recommendations to address observed gaps. The approach used to meet these objectives is a water resources assessment from the landscape to the basin-scale. This is to understand the current practices on water management through field observation, stakeholder consultations, and the analysis of existing data and literature on water resources of the basin. Field observations were conducted on selected learning watersheds in three sub-basins: Borkena, Mille and Awash Terminal. The specific watersheds are Felana, Lake Maybar and Gelana, and Ewa and Afambo. The key challenges to water resources management that were observed at basin, sub-basin and watershed levels are: (1) inadequate data and information on key hydrological variables that led to a lack of recent knowledge on water availability, actual water use, types and potentials of water sources; (2) lack of decision-support tools that would provide strategic and operational level information for risk-based planning and management of water resources (3) lack of appropriate water infrastructure and context-specific technologies that can support small-scale producers (SSPs) and basin-level water managers; (4) lack of well-coordinated institutions to govern and manage water resources from catchment to basin levels; and (5) lack of technical skills and knowledge on how to monitor water availability, water use, and the application of tools. The implications of these challenges are visible in water scarcity observed during dry seasons for different sectors; low agricultural productivity; upstream-downstream tension on water; flooding damages in peak rainfall seasons; and deterioration in water quality that impacts agriculture and drinking water supply. This study finds out that the practice of water resources management in the basin requires substantial strengthening to make it climate resilient. The study proposes strategies that would help in making climate-smart water resources management practices in the basin. Climate-smart water resources management is defined as the practice that would maximize the goods and services that can be produced from limited water resources; minimize the impact of climate extremes - floods and droughts at multiple scales; curtail the impact of rainfall variability on small-scale producers, and enhance water resources planning and management at the basin-scale. To achieve these goals, the study proposes to utilize five strategies which are: (1) improving availability and access to timely and context-specific climate and water information services that are well coordinated across sectors; (2) enhancing water use efficiency and productivity at multiple scales and sectors; (3) promoting integrated water storage use and management; (4) improving climate-resilient water governance; and (5) multilevel and inclusive capacity development. The adoption and implementation of these strategies are envisaged to facilitate effective sustainable water resources management in the Awash Basin.